Evaluation of Reliability of Safety Instrumented System (SIS) and Safety Valves of Crude Oil Separators in an Oil Field - Shaluf, Ibrahim; Sakal , Salem (University of Zawia Journal of Engineering Sciences and Technology, 2023)
Crude oil separator is a pressure vessel used to separate oil and gas from oil well stream. The separators are provided with Basic Process Control System (BPCS) and protection system which consist of Safety Instrumented System (SIS) and Pressure Relief System (PRS). Failure of the crude oil separator might result in fire, explosion and toxic dispersions. The world has witnessed several fire and explosion incidents due to operation of crude oil separators. Reliability of the control and protective systems of crude oil separator is very important to verify their abilities to perform their functions. This technical article presents an overview on the layers of protection of crude oil separator and the reliability of protective systems. The article also presents an evaluation of reliability of SIS and safety valves of crude oil separators in an oil field. The crude oil separators are arranged in the form of three parallel trains of separators each train divided into three stages. The first stage consists of two separators and each stage of second and third stages consist of one separator. The reliability of the different configurations of the SIS and safety valves of a train of production separators has been estimated and found to be acceptable.